Structural safety evaluation of adhesive bonds: A fracture analytical approach. (May 2021) - Brandtner-Hafner, Martin
Highlights: A novel safety parameter-based concept based on three fracture metrics was introduced. Much more authentic evaluations were possible compared to standardized test setups. Enhancement of explanatory power compared to technical datasheets was achieved. Novel safety parameters for guiding decision-makers were ascertained. Peer-Safety portfolios were introduced for optimizing adhesive evaluation. Abstract: When it comes to evaluating adhesive bond performance and safety, different approaches are known. Whilst mechanical lab tests strive to measure pure bond strength via lap- shear or peel stress, fracture mechanics goes one step further. There, fracture toughness is the ultimate failure criterion indicating a materials' resistance against crack propagation. However, almost countless competing approaches, measures and, concepts from literature make safety evaluation of adhesively bonded structures a challenging task. This study aims to provide a fracture analytical evaluation approach by analyzing the structural integrity of adhesively bonded structures. To achieve this, a novel set of safety metrics both on a technical and economical basis were introduced. Experiments on three structural adhesives were conducted to demonstrate the practicability of this method for quality and safety control. Results unveil a significant gain of information about the techno-economic safety and performance of adhesive-bonded structures compared to data provided in technical data sheets giving clarity to decision-makers for their adhesive selection.